Improvement of three-level code division multiplexing in optical fiber communication - Khosravi, Faranak (2013)
Three-level code division multiplexing (3LCDM) is a multiplexing technique that owes the advantages of both return to zero (RZ) and non return to zero (NRZ) techniques. The principle work of 3LCDM is based on the multiplexing of two users with each user utilizing different line coding techniques of RZ and NRZ. Both users share this communication medium to transmit the same carrier wavelength concurrently. By using 3LCDM technique over wavelength division multiplexing (WDM), the channel capacity can be doubled. However, this technique faces a major problem due to its three-level properties especially when the optical amplifier is used in long distance system. Since the noise is intensity dependent, the signals having a higher power level experience more noise as compared to the signals having lower power level. This difference causes dissimilar performance for 3LCDM users and degrades the system’s performance. Dispersion is another problem that is experienced when using this technique. It broadens the width of signal pulse in the fibre due to its dependence on the fibre material’s refractive index on the optical carrier wavelength. Therefore, this study aims to overcome these two problems peculiar to 3LCDM system by applying level spacing optimization and dispersion mapping. This study was conducted using OptiSystem software interfaced with Matlab environment. In simulating the level of the spacing optimization setup, the level spacing of the upper and lower bounds of 3LCDM were controlled using two techniques, i.e., optical and electrical configurations. For dispersion mapping, periodic mapping was used for the simulation which included the effects and interactions between attenuation, dispersion, and self-phase modulation (SPM). The performance of the system in this study was observed and evaluated. It was found that by using the level spacing optimization method for both optical and electrical configurations,3LCDM system was improved by around 4.5 dB in OSNR and 3.5 dB enhancements in receiver sensitivity. The differences between the two techniques of optical and electrical configuration were observed by comparing chromatic dispersion tolerance. The observation showed that in electrical configuration, both users could tolerate the maximum dispersion of ± 89 ps/nm. Meanwhile, in optical configuration, dissimilar dispersion tolerances were observed in positive and negative dispersions, where such tolerances remained between around + 88 and - 69 ps/nm respectively. Optical configuration is still more robust compared to NRZ chromatic dispersion tolerance. By applying the dispersion map, the performance has improved by 5.5 dB in OSNR, 6 dB in receiver sensitivity and 3 dB in self phase modulation (SPM) threshold. Based on these improvements, the performance of 3LCDM is comparable to the available multiplexing and modulation techniques while offering simpler transmitter and receiver architecture. When chromatic dispersion tolerance of 3LCDM system and NRZ are compared, it can be concluded that the worst channel of 3LCDM technique has a better performance of ± 42 ps/nm than that of NRZ. Hence, 3LCDM technique is suitable to be implemented in WDM transmission systems.